2010
DOI: 10.1111/j.1365-2265.2009.03688.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hormonal contraceptives on bone turnover markers and bone health

Abstract: SummarySex hormones are important regulators of bone metabolism. As hormonal contraceptives contain either oestrogens or progestins, or a combination thereof, it is conceivable that these widely used agents have an effect on bone metabolism and bone health. The main users of hormonal contraceptives, adolescent girls and young women, are still building bone and accruing bone mass and may therefore be particularly susceptible to the effects of hormonal contraceptives on bone. Despite these concerns, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 91 publications
(121 reference statements)
1
19
0
6
Order By: Relevance
“…This conclusion is consistent with a recent study that reviewed 18 studies with six crosssectional and 12 longitudinal studies documented in the literature until January 2009, which concluded that use of OC is associated with a significant reduction in most but not all markers of bone turnover, although this did not appear to translate to any reduction in fractures [25].…”
Section: Bone Turnover Markerssupporting
confidence: 91%
“…This conclusion is consistent with a recent study that reviewed 18 studies with six crosssectional and 12 longitudinal studies documented in the literature until January 2009, which concluded that use of OC is associated with a significant reduction in most but not all markers of bone turnover, although this did not appear to translate to any reduction in fractures [25].…”
Section: Bone Turnover Markerssupporting
confidence: 91%
“…This is an important consideration for long-term management of patients using PEGLA as a contraceptive. Currently, both the combined oral hormonal contraceptives (COC) and progestin-only contraceptives (POC) are associated with changed bone metabolism, including decreased bone turnover (COC, POC) and bone resorption (POC) [46]. By contrast, the progestin-releasing intrauterine device Mirena is not associated with reduced bone mineral density [47], likely because systemic levels of progestin are minimized by the local site of administration and the reduced dose required.…”
Section: Discussionmentioning
confidence: 99%
“…Ethinyl estradiol, used in most oral contraceptive pills, is a potent synthetic E2 analog that is not metabolized to E2 (Klein et al, ). Use of oral contraceptives for HRT is generally not recommended in young women with Turner syndrome; EE is the least physiologic and potential adverse effects include higher blood pressure, insulin resistance, and it may also be suboptimal for bone health (Herrmann & Seibel, ). Exceptionally, young women with Turner syndrome mosaicism who have spontaneous cycles and desire contraception, may wish to use oral contraceptives containing EE.…”
Section: Endocrine Issuesmentioning
confidence: 99%